An integrated total neutron scattering – NMR approach for the study of heterogeneous catalysis. Issue 72 (23rd August 2018) - Leutzsch, Markus; Falkowska, Marta; Hughes, Terri-Louise; Sederman, Andrew J.; Gladden, Lynn F.; Mantle, Michael D.; Youngs, Tristan G. A.; Bowron, Daniel; Manyar, Haresh; Hardacre, Christopher
Abstract : By combining total neutron scattering with nuclear magnetic resonance (NeuNMR) in a single experimental apparatus, new insights into the kinetics and mechanisms of heterogeneous catalytic reactions occurring in situ, within the catalyst pore space, are possible. Abstract : Nuclear magnetic resonance (NMR) and total neutron scattering techniques are established methods for the characterisation of liquid phases in confined pore spaces during chemical reactions. Herein, we describe the first combined total neutron scattering – NMR setup as a probe for the catalytic heterogeneous reduction of benzene- d 6 with D2 in 3 wt% Pt/MCM-41.